Minecraft : the Survivors' book of secrets - Milton, Stephanie (Del Rey, 2016)
"An all-new official Minecraft guidebook full of tips to fend off mobs and withstand the wild! This official Minecraft book contains the collective knowledge of the Survivors: an underground group of Minecraft experts who have been around since the days of Alpha"--Amazon.com.